Cultural Validity as Foundational to Assessment Development: An Indigenous Example - Kūkea Shultz, Pōhai; Englert, Kerry (Frontiers in Education, 2021)
The state of Hawai‘i has a linguistically and culturally diverse population that recognizes Hawaiian and English as official languages. Working with the community, the state established the Hawaiian Language Immersion Program, Ka Papahana Kaiapuni Hawai‘i (Kaiapuni), to support and promote the study of Hawaiian language, culture, and history. Kaiapuni students are historically marginalized test-takers and had been assessed using instruments that were culturally and linguistically insensitive, contained construct irrelevant variance, or had inadequate psychometric properties (Kaipoleimanu Ka‘awaloa, 2014; U.S. Department of Education, 2006). In response, the Hawai‘i State Department of Education and the University of Hawai‘i developed the Kaiapuni Assessment of Educational Outcomes (KĀʻEO), which engages Kaiapuni students in technically rigorous, Native language assessments. This article details the theoretical framework of the KĀʻEO program, which includes traditional validity studies to build content and construct validity that support the assessment’s use for accountability. However, the KĀʻEO team recognized that additional evidence was needed because the KĀʻEO theory of change is grounded in principles of community use of assessment scores to advance cultural and language revitalization. The article provides an example of one of the validity studies that the team conducted to build evidence in support of cultural and content validity.